If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(n + -2) + 2(n + 1) = 0 Reorder the terms: -5(-2 + n) + 2(n + 1) = 0 (-2 * -5 + n * -5) + 2(n + 1) = 0 (10 + -5n) + 2(n + 1) = 0 Reorder the terms: 10 + -5n + 2(1 + n) = 0 10 + -5n + (1 * 2 + n * 2) = 0 10 + -5n + (2 + 2n) = 0 Reorder the terms: 10 + 2 + -5n + 2n = 0 Combine like terms: 10 + 2 = 12 12 + -5n + 2n = 0 Combine like terms: -5n + 2n = -3n 12 + -3n = 0 Solving 12 + -3n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3n = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -3n = 0 + -12 -3n = 0 + -12 Combine like terms: 0 + -12 = -12 -3n = -12 Divide each side by '-3'. n = 4 Simplifying n = 4
| (4z/9zz)x(3z/2z) | | 4-4x=-4 | | 8x-15x=3x-40 | | 2x^2-15x+10=0 | | 7(g-2)=3k+6 | | 1/2y=1/2 | | 4x-(8x-9)= | | 2x-5=2x+(x+2) | | 90+18m= | | 3(4n+5)=-723 | | -10(b-5)=-90 | | 85=-5x-5(x-3) | | 3rs-8r+s-8rs+14r-s= | | 11+2(6y+2)= | | 8x+12=85 | | 10=3/4x+36 | | Y=-23+4y | | 3/4(12x-8)=-6 | | 4x+17.5=49.5 | | 4/7(2-x)=8 | | 5x^2-3x-4-7x+8-4x^2= | | 5(3+10u)= | | X*54=100 | | -10(b-5)=-70 | | 1/2x-4=-1/2x+4 | | Y=2(2y-12)+1 | | 7x-3.5=28 | | x+0.00398x=1 | | -10(b-5)=-60 | | -10(b-5)=-50 | | Y=2(2y-12) | | X-3y=41 |